Utility of electrophysiologic testing for sudden death risk stratification in cardiac sarcoidosis patients with mildly impaired left ventricular function. (January 2022) - Tandon, Pranai; Mosleh, Tayseer; Mustafa, Ali; Miodownik, Hope; Miller, Marc; Morgenthau, Adam S.
Abstract: Background: Ventricular arrhythmias (VA) account for at least 25% of deaths caused by cardiac sarcoidosis (CS) and may arise in patients with mildly impaired LVEF (>35%). Objective: In the current study, we examine whether EP study may be used for sudden death risk stratification in CS patients who have mildly impaired LVEF and a diagnosis of highly probable or probable CS according to the World Association of Sarcoidosis and Other Granulomatous Diseases Sarcoidosis Organ Assessment Instrument (WASOGI). Methods: All patients: (1) exhibited a diagnosis of highly probable or probable CS according to the WASOGI, (2) exhibited cardiac MRI findings consistent with CS, (3) exhibited LVEF >45% and (4) underwent EP study. Device interrogations, transmissions and medical records were reviewed for all patients. Results: We identified 46 CS patients with mildly impaired LVEF. VA were induced in 11 patients and 10/11 patients underwent ICD placement. Thirty-five patients had no VA and 24/35 patients underwent placement of an ILR. During the follow-up period, the VA event rate was 6.5%. The negative and positive predictive values of the EP study for the development of VA were 100% and 27.2%, respectively. Conclusions: In CS patients with mildly impaired LVEF and a diagnosis of highly probable or probable CS, a negative EP study was highly predictive of the absence of VA. The successful execution of future prospective studies is contingent upon enrollment of phenotypically homogenous cardiac sarcoidosis patients. Highlights: PES during (EP) study may be used for the purposes of sudden death risk stratification in cardiac sarcoidosis patients with mildly impaired LVEF. EP study positive patients were more likely to have an abnormal EKG (91% versus 60% p = 0.056) at the time of EP study. A negative EP study appears to be highly predictive of the absence of VA.